THE VALUE OF GRAY-SCALE MEDIAN OF CAROTID PLAQUE IN PREDICTING THE PROGRESSION FROM TRANSIENT ISCHEMIC ATTACK TO CEREBRAL INFARCTION - WANG Limin, HAN Dongming (精准医学杂志, 2023)
Objective To investigate the value of gray-scale median (GSM) of carotid plaque in predicting the progression from transient ischemic attack (TIA) to cerebral infarction. Methods The clinical data of 156 patients with carotid plaque who were admitted to our hospital from February 2020 to March 2022 was collected. The patients were divided into TIA group and non-TIA group according to their history of TIA. The two groups were compared for differences in the volume, thickness, and GSM of carotid plaque. The patients with different clinical features in the TIA group were compared for differences in the volume, thickness, GSM, and ABCD2 score of carotid plaque. The incidence of cerebral infarction within one year in the patients with TIA was recorded. The receiver operating characteristic (ROC) curve was used to analyze the value of GSM in predicting cerebral infarction. Results Compared with the non-TIA group, the TIA group had a significantly reduced GSM value (t=2.638,P<0.05). There were significant differences in the GSM and ABCD2 score of carotid plaque between patients with different durations and numbers of attacks in the TIA group (t=2.271-3.324,P<0.05). Compared with patients in the TIA group who did not expe-rience any cerebral infarction within one year, patients with cerebral infarction within one year showed a significant decrease in GSM and a significant increase in ABCD2 score (t=3.494,2.435,P<0.05). The ROC analysis showed that the areas under the ROC curves of GSM and ABCD2 score of carotid plaque for predicting cerebral infarction in patients with TIA were 0.765 and 0.739, respectively. Conclusion The GSM value of carotid plaque in patients with TIA significantly decreases and relates to the aggravation and progression of the disease to cerebral infarction within one year, making GSM similarly valuable to ABCD2 score in predicting cerebral infarction.